“Congratulations! You Are Now the Happy Owner of a University”. Review of the book: H. Rosovsky (2015) Universitet: Rukovodstvo dlya vladeltsa [The University: An Owner’s Manual]. Moscow: HSE. - Chirikov, Igor (Voprosy obrazovaniya / Educational Studies Moscow, 2015)
Having worked as the Dean of the Faculty of Arts and Sciences at Harvard University for a long time, Henry Rosovsky summarizes his experience and suggests a “university owner’s manual” to be studied by students, teachers, administrators, and the public. Being mostly a journalistic style and ironic, the book however addresses the fundamental aspects of life in modern universities. The review singles out four principal storylines that are being analyzed through the lens of the current trends and empirical data about Russian higher education. Those are issues of 1) using objective vs. subjective criteria in admission of students; 2) focusing on general vs.specialized education; 3) choosing between teaching-oriented and research-oriented faculty; 4) bringing in professional or academic administrators to run the university. Despite the fact that the book was written over 25 years ago and is devoted to Harvard, Rosovsky’s ideas are still important. His strong belief in the necessity to develop a collective responsibility of students, teachers and administrators for the life and the future of a university is timely for Russian higher education.